Perancangan Enterprise Architecture Pada Rumah Sakit Umum Harapan Ibu Purbalingga Menggunakan Framework TOGAF - Tarwoto; Elsa Ayunda Pratiwi; Annisa Suci Octavia; Adinda Arininta Loysiana; Falia Nur Afifah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The development of information technology (IT) is very important in improving the efficiency and quality of health services in public hospitals, such as RSU Harapan Ibu Purbalingga. The TOGAF framework (The Open Group Architecture Framework) offers a structured approach to designing, managing and implementing IT architecture. This research explores the application of TOGAF in IT infrastructure planning at RSU Harapan Ibu to improve operational efficiency and service quality. The methods used include IT requirements analysis, TOGAF-based architectural modeling, and architectural implementation evaluation. The research results show that implementing TOGAF can increase the speed of access to patient information and optimize hospital operations.